NEW DATA OF TWO Coomansus SPECIES (Mononchida: Mononchidae) FOR NEMATODE FAUNA IN VIETNAM - TAM, VU THI THANH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2018)
Two species of Coomansus, C. arvensis (Eroshenko, 1972) Jairajpuri & Khan, 1977 and C. ouinnensis (Yeates, 1992) Andrassy, 1993 were recorded, described and illustrated for the first time from Vietnam. Coomansus arvensis was collected from Phia Oac natural reservation area, Cao Bang province, their measurements and description correspond well with the type population from Far-East, Russia except for a slightly slenderer body (a = 27-28 vs 17-21); they also agree with the specimen from Uttarakhand, India apart from a slightly shorter tail and a slightly narrower lip region width. Coomansus ouinnensis was found in Hoang Lien National Park, Lao Cai province. Measurements and description of the Vietnamese specimens fit well the type population from Ouinne Valley as well as population from Mt Dzumac (New Caledonia) with the exception for a slightly higher than in C’ ratio (c’ = 4.5 vs 3.2-3.5) and slightly higher position of apex of dorsal tooth from the base of buccal cavity(86-87% vs 73-79%).